Dystocia due to Schistosomus Reflexus Foetal Monstrosity in a Jaffarabadi Buffalo: A Case Report - N Borakhatariya, Devasee; N Kethavath, Giri; R Nandaniya, Nirbhay; J Savaliya, Krinal; B Gadhadara, Ashish; M Sanghani, Yash (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Among buffalo breeds, Jaffarabadi is the heaviest and most commonly suffers from dystocia for a variety of reasons, including uterine torsion, incomplete cervical dilatation, an oversized foetus, dropsical conditions of the foetus and foetal membranes, and congenital foetal monstrosities such as schistosomus reflexus. Several authors reported the prevalence of the schistosomus reflexus foetal monster in many species, i.e., cattle, buffalo, sheep, goat, dog, and equine (Kumar et al., 2019a,b; Duarte et al., 2022; Deepak et al., 2023; Harika et al., 2023; Yadav et al., 2024). The presence of a deformed spine and exposed abdominal and thoracic viscera allows for the gross identification of schistosomus reflexus. Anomalies of the ovum, embryo, or foetus that result in skeletal developmental abnormalities are typically cited as the etiology for the emergence of foetal monstrosities, however, definite etiology is still ambiguous (Munif et al., 2023). The majority of affected foetuses are not viable. Congenital defects are seen as economically significant since they hinder spontaneous foetal delivery. Dystocia is inevitable in the cases of the foetal monstrosities amongst farm animals (Borakhatariya et al., 2017; Borakhatariya et al., 2020). In such instances, cases can be managed by Caesarean section when there is insufficient space in the birth canal to apply manual obstetrical mutations, or by partial or complete foetotomy for per-vaginum delivery. Such cases need to be treated promptly because if they are not, the dead foetus may develop emphysema, which could lead to toxaemia and the collapse of the dam. An unusual case of dystocia due to schistosomus reflexus foetal monster clinically managed with Caesarean section in a Jaffarabadi buffalo is described in this case report.